PECULIARITY OF RADIONUCLIDES ACCUMULATION IN VARIOUS ORGANS OF VEGETABLE CROPS - A. V. Soldatenko; V. F. Pivovarov; E. G. Dobrutskaya (Овощи России)
The peculiarities of accumulation of radionuclides 137Cs and 90Sr in different organs and tissues of vegetable crops have been studied. Aim of this research was the enhancement of safety and quality of food at the cost of the elimination from the food ration of the vegetable organs with high ability to accumulate the radionuclides